The relationship between students’ subject preferences and their information behaviour - Madden, Andrew D; Webber, Sheila; Ford, Nigel; Crowder, Mary (Journal of documentation, 2018)
Purpose The purpose of this paper is to investigate the relationship between preferred choice of school subject and student information behaviour (IB). Design/methodology/approach Mixed methods were employed. In all, 152 students, teachers and librarians participated in interviews or focus groups. In total, 1,375 students, key stage 3 (11-14 years) to postgraduate, responded to a questionnaire. The research population was drawn from eight schools, two further education colleges and three universities. Insights from the literature review and the qualitative research phase led to a hypothesis which was investigated using the questionnaire: that students studying hard subjects are less likely to engage in deep IB than students studying soft subjects. Findings Results support the hypothesis that preferences for subjects at school affect choice of university degree. The hypothesis that a preference for hard or soft subjects affects IB is supported by results of an analysis in which like or dislike of maths/ICT is correlated with responses to the survey. Interviewees’ comments led to the proposal that academic subjects can be classified according to whether a subject helps students to acquire a “tool of the Mind” or to apply such a tool. A model suggesting how IB may differ depending on whether intellectual tools are being acquired or applied is proposed. Practical implications The “inner logic” of certain subjects and their pedagogies appears closely linked to IB. This should be considered when developing teaching programmes. Originality/value The findings offer a new perspective on subject classification and its association with IB, and a new model of the association between IB and tool acquisition or application is proposed, incorporating the perspectives of both teacher and student.